Analisis Komparasi Pendapatan Agroindustri Gula Aren dan Gula Semut (Studi Kasus Kelompok Tani Mutiara Di Kecamatan Lareh Sago Halaban Sumatera Barat) - Yelfiarita Yelfiarita; Wimby Filiani; Veronice Veronice (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Nira is the main derivative product of Aren palm. Making Aren palm to be palm sugar and granulated palm sugar will increase the benefit of Aren Palm and increase the farmer's income. It is needed towards perform comparison research for agroindustrial revenue of palm sugar and granulated palm sugar to make sure that it may be a referral for the farmer in picking an extra rewarding diversification of Aren palm. This research strives to review the incorporated revenue from palm sugar and granulated palm sugar services and examine the evaluation of the usefulness amount of palm sugar and granulated palm sugar services. The study was performed in January - April 2021 for all participants of the "Mutiara" Farmers Team in Lareh Sago, Halaban Area, which was energetic in generating palm sugar and granulated palm sugar in the final year. The review of the research makes use of revenue and also earnings review. The study's results concluded that palm sugar income amounted to Rp. 671,741/month, while granulated palm sugar amounted to Rp. 860,891/month. This study shows that granulated palm sugar's income is 12.34% higher than palm sugar. In terms of the R/C ratio, producing Nira in granulated palm sugar (R/C ratio = 2.53) is much more feasible than processing it into palm sugar (R/C ratio = 1.76). Last but not least, this study concludes that producing granulated palm sugar is more profitable than palm sugar. It is an excellent business to be developed for adding income for the farmer.